Cytometric cell-based assays for anti-striational antibodies in myasthenia gravis with myositis and/or myocarditis - Kufukihara, Kenji (Sci Rep, 2019)
The purposes of the present study were to identify anti-striational antibodies in myasthenia gravis (MG) patients with myositis and/or myocarditis using a combination of cell-based assays and flow cytometry (cytometric cell-based assays) and to describe the main clinical implications. Among 2,609 stored samples collected from all over Japan between 2003 and 2016, we had serum samples from 30 MG patients with myositis and/or myocarditis. Cytometric cell-based assays with titin, ryanodine receptor, and voltage-gated Kv1.4 were performed. Autoantibodies were determined by differences in phycoerythin fluorescence between the 293F cells and titin-transfected cells. MG patients with myositis and/or myocarditis as well as late-onset and thymoma-associated MG had anti-titin, anti-ryanodine receptor, and anti-Kv1.4 antibodies. In contrast, patients with early-onset MG, those with other myopathies and healthy controls did not have anti-titin or anti-Kv1.4 antibodies with some exceptions, but they possessed anti-ryanodine receptor antibodies. Thirty MG patients with myositis and/or myocarditis showed a severe generalized form, and 21 of them had thymoma. Anti-titin and anti-Kv1.4 antibodies were found in 28 (93%) and 15 (50%) patients, respectively, and all patients had at least one of these antibodies. Cytometric cell-based assays thus demonstrated that anti-striational antibodies are biomarkers of MG with myositis and/or myocarditis.